Emotion recognition deficits in patients with skin picking disorder: the role of alexithymia while controlling depression, and anxiety levels - Ergelen, Mine; Taşlıoğlu Sayıner, Aliye Canan; Çırakoğlu, Mustafa; Yalçın, Murat (Frontiers in Psychiatry, 2025)
ObjectiveSkin Picking Disorder (SPD) has been associated with higher levels of alexithymia, a condition that predicts self-injurious behaviors, a core feature of SPD. Recent studies have expanded the understanding of alexithymia beyond deficits in emotional awareness, highlighting its role on the ability to recognize and process others’ emotions. This study aimed to explore how emotion recognition abilities differ in individuals with varying levels of alexithymia and the presence of SPD.MethodsThis cross-sectional case-control study included 45 individuals diagnosed with SPD and 47 controls. Participants were assessed through the Toronto Alexithymia Scale, the Facial Emotion Recognition Test, the Beck Depression Inventory, and the Beck Anxiety Inventory. Two-way analysis of covariance tests were conducted to evaluate the effects of SPD diagnosis and alexithymia levels on facial emotion recognition tasks, while controlling for anxiety and depression.ResultsIndividuals with Skin Picking Disorder (SPD) showed significant impairments in recognizing fear, neutral expressions, and surprise compared to controls. SPD was linked to lower fear recognition accuracy, while both SPD and higher alexithymia were associated with poorer recognition of neutral expressions and surprise. No significant differences were found for happiness, sadness, anger, or disgust. No interaction effects were observed between SPD and alexithymia for any emotion.ConclusionsThis study enhances the understanding of emotion recognition in SPD and alexithymia by highlighting their shared and unique challenges. The absence of a significant interaction effect suggests that these conditions independently contribute to emotion recognition deficits without compounding effects, underscoring the need for targeted interventions.